THE PHENOMENON OF FEMALE LEADERSHIP IN WESTERN SOCIO-POLITICAL THOUGHT: THEORETICAL CONCEPTS AND PRACTICAL APPROACHES - Kholikulova Khulkar Yuldashevna (Innovate Conferences, 2025)
The issue of social equality between women and men, the elimination of gender discrimination, and the development of socio-political and cultural attitudes aimed at protecting women's rights have a long historical background. The origins of feminism date back to the late 18th century, when women's rights began to be actively discussed in Europe and North America. One of the earliest and most influential documents reflecting feminist ideas was Mary Wollstonecraft’s A Vindication of the Rights of Woman (1792), in which she advocated for women's education and asserted their right to equal treatment.